IMPLEMENTASI PROGRAM PEMBERDAYAAN PEREMPUAN MELALUI BIDANG USAHA INDUSTRI KECIL (Studi Di Gampong Matang Meunye Kecamatan Syamtalira Aron Kabupaten Aceh Utara) - Lisa Iryani (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
The title of this research is the implementation of women's empowerment programs through small industrial enterprises. Study in Matang Meunye Village, Syamtalira Aron District, North Aceh Regency. Study in Matang Meunye Village, Syamtalira Aron District, North Aceh Regency. The problem that occurs in this study is that not all people are involved in managing small industrial businesses, only some people are able to manage small industrial businesses. The focus of this research is the success factor of implementing empowerment programs through small industrial businesses related to communication, resources, disposition and bureaucratic structure and obstacles in small industrial businesses. This study uses a qualitative approach with data collection techniques through observation, interviews and documentation, with 8 informants. The results showed that in the implementation of women's empowerment programs through small industrial businesses, the government was still not maximal in the implementation and implementation of the empowerment, the biggest problems were the socialization that had not been fully completed, the resources were still low in both the budget and human resources. The obstacle faced is that in the rainy season it will result in losses and limited capabilities in the marketing aspect. The obstacle faced is that in the rainy season it will result in losses and limited capabilities in the marketing aspect. The suggestion from the writer in this research is that it is hoped that the policy implementers will be able to open alternative insights about how to cope with the tempe cracker industry business during the rainy season so that in the rainy season this business will continue to run. And it is hoped that the party implementing the policy will provide insight as well as provide an example of good marketing and attract many customers so that the business can move in well-known markets.